Adherence and Beliefs to Adjuvant Hormonal Therapy in Patients with Breast Cancer: A Cross-Sectional Study (Conference Paper) # - Saad, Anwar Habeeb; rabeea, Ihsan; Salih, Haider (Iraqi Journal of Pharmaceutical Sciences, 2022)
Breast cancer is the most common cancer among women over the world. To reducing reoccurrence and mortality rates, adjuvant hormonal therapy (AHT) is used for a long period. The major barrier to the effectiveness of the treatment is adherence. Adherence to medicines among patients is challenging. Patient beliefs in medications can be positively or negatively correlated to adherence. Objectives: To investigate the extent of adherence and factors affecting adherence, as well as to investigate the association between beliefs and adherence in women with breast cancer taking AHT. Method: A cross-sectional study included 124 Iraqi women with breast cancer recruited from Middle Euphrates Cancer Center. Morisky medication adherence scale (MMAS) and beliefs about medication questionnaires (BMQ) are used to assess adherence and beliefs respectively. Result: 25% of women were fully adherent (MMAS = 8). 83.06% of all women developed side effects from medications received. Side effects and unemployed women were significantly associated with non-adherence. Additionally, there is no significant association between beliefs in medications and adherence. conclusion The enormous percent of poor adherence caused by side effects suggests the need for interventions by educating patients about the importance of their treatment and how to overcome side effects.